Práticas de vermicompostagem e educação ambiental em escolas públicas de educação integral em tempo ampliado de Curitiba - PR - Zago, Marcia Regina Rodrigues da Silva (2021)
This thesis deals with vermicomposting and Environmental Education public schools of Elementary School I (1st year to 5th year) of Education in Extended Time in the city of CuritibaPR. Teachers at these institutions worked with the students on vermicomposting practices, under the guidance of the researcher, to introduce ideas for reusing organic waste produced in schools. In the contemporary world, the production and consumption of artifacts and food generate increasing amounts of waste that need to be managed and align with the principles of sustainability and the social and environmental commitments proclaimed by Environmental Education (EA). The general objective of this Thesis was to propose a set of vermicomposting and AE actions and initiatives, with organic waste produced in schools, associated with the teaching and learning process. The methodology, of a qualitative nature, privileged the microprocess of organic waste management through analysis and detailed, descriptive and narrative studies, of the actions and data collected. After a bibliographical survey, the researcher contacted the schools and received acceptance to carry out the field research. First, conversation workshops were held to demonstrate the importance of research, create bonds of trust and ensure the objectivity and scientific neutrality of practices. Then, contacts were made with public authorities, and UTFPR, which collaborated with the donation of vermicomposting boxes. Eight teachers received this technical object in the eight schools, which also became the object of teaching and learning. The practices took place in stages. Four types of waste were separated and weighed by teachers and students for 30 days. The results showed that it was necessary to understand the weaknesses of the issues of production, separation and disposal of organic waste. Vermicomposting practices were introduced with the reuse of organic waste produced in schools. The activities made it possible to assign meanings to interdisciplinarity and transversality as motives for discoveries and scientific studies of biology, mathematics, geography, history, Portuguese and art. They gave a new guise to the ways of thinking and acting on educational, sócio-environmental issues and on the living beings that are part of the Planet. The appropriation of knowledge and knowledge by students and teachers strengthened the use of reason and the unveiling of myths. The final considerations of the Thesis refer to the consolidation of the research space conquered by the researcher, with the activities of vermicomposting and environmental education, in municipal schools. The search for objectivity of the investigated problem introduced new referents for this type of didacticpedagogical activity, among them the interaction of the interlocutors and the recontextualization of doing science.